A modified binary composite bipolar plate for vanadium battery and preparation method thereof
By using the shell polycogen film to cover the carbon nanotubes and carbon graphite in the bipolar plates of the whole pyrine stream battery, and the interface is coupling, it solves the existing bipolar board on the conductivity, mechanical strength and corrosion resistance of the bipolar board The deficiencies have achieved more efficient conductivity and mechanical strength, extending the service life and improving the efficiency of electricity.
Patent Information
- Application Number
- CN202411590668.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing all-vanadium flow battery bipolar plates have shortcomings in electrical conductivity, mechanical strength, chemical oxidation resistance and electrochemical corrosion performance, resulting in low energy efficiency of the stack and short service life.
The modified dual -compound bipolar plate is used to cover the carbon nanoprobus and carbon covering graphite through the shell poly glucose film, combined with an enhanced siane coupling agent for interface coupling, forming an efficient conductive network and mechanical intensity structure.
It improves the conductivity and mechanical strength of the bipolar board, reduces the resistivity, enhances corrosion resistance, extends the service life of the bipolar board, and improves the efficiency of the total liquid flow battery pile.
Smart Images

Figure CN119108575B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of all-vanadium liquid flow battery bipolar plates, and in particular to a modified binary composite bipolar plate for a vanadium battery and a preparation method thereof. Background Art
[0002] In the all-vanadium liquid flow battery system, the battery stack composed of multiple single cells connected in series is the core component, and the single cell is composed of key components such as bipolar plates, current collectors, ion conduction membranes, electrodes and end plates. Improving the performance of key components of single cells has become an important part of the development of liquid flow batteries.
[0003] As the conductive and mechanical support component in the all-vanadium liquid flow battery system, the bipolar plate can collect and conduct the current generated during the battery charging and discharging process, connect multiple single cells and prevent the mixing of positive and negative electrolytes and direct contact of electrodes, which has a significant impact on the energy efficiency of the battery stack. Due to the highly corrosive electrolyte environment in which it is located, it is required to have good conductivity, mechanical strength, chemical oxidation resistance and electrochemical corrosion resistance. The main types of bipolar plates currently include metal bipolar plates, graphite bipolar plates and polymer-carbon composite bipolar plates. Among them, metal bipolar plates are expensive and have poor corrosion resistance; although graphite bipolar plates have excellent conductivity, they have low toughness and are easy to break during processing and installation; polymer-carbon composite bipolar plates have good mechanical properties, but their resistivity is relatively high. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a modified binary composite bipolar plate for vanadium battery and a preparation method thereof.
[0005] The technical solution adopted by the present invention is as follows:
[0006] A method for preparing a modified binary composite bipolar plate for a vanadium battery comprises the following steps:
[0007] Step S1: dispersing carbon nanotubes, chitosan and heteropolysaccharides in an acetic acid solution, and adding an alkali solution and a surfactant thereto to adjust the pH to 9-13 to obtain a precursor solution; placing the precursor solution in a water bath, and adding a crosslinking agent thereto to carry out a crosslinking reaction, and after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes;
[0008] Step S2: dispersing graphite powder and cationic polyelectrolyte in an organic solvent, then adding anionic polyelectrolyte thereto and stirring and reacting under the protection of an inert gas, filtering and washing the obtained product, and transferring it to an oven for drying, and then heat-treating the obtained product under the protection of an inert gas to obtain carbon-coated graphite;
[0009] Step S3: grinding and dispersing chitosan film-coated carbon nanotubes and carbon-coated graphite to obtain a mixed binary carbon material, and dispersing the mixed binary carbon material in an enhanced silane coupling agent aqueous solution and stirring to disperse the mixed binary carbon material, then adding a hydrolysis catalyst thereto and continuously stirring the mixed binary carbon material, and transferring the mixed binary carbon material to an oven for drying and heat treatment after the reaction is completed to obtain a paste slurry;
[0010] Step S4: First, disperse the resin powder and the polymer additive in an organic solvent, and perform preliminary melt mixing in an internal mixer to obtain internal mixer particles 1. Then, the internal mixer particles 1 and the paste filler and the compatibilizer are melt mixed again in the internal mixer to obtain internal mixer particles 2. The internal mixer particles 2 are transferred to a mold and integrally pressed with a hot press to obtain a modified binary composite bipolar plate.
[0011] Preferably, in step S1, the heteropolysaccharide is one of hyaluronic acid, chondroitin sulfate, agar and peptidoglycan; the volume concentration of the acetic acid solution is 1%-5%; the alkali solution is one of ammonia solution, sodium carbonate solution, sodium hydroxide solution and triethylamine solution, and the concentration is 0.5-2 mol / L; the surfactant is one of dodecyl dimethyl betaine, 3-sulfopropyl dodecyl dimethyl betaine, dodecyl aminopropionic acid and tetradecanoyl amide propyl hydroxypropyl sulfobetaine; the mass ratio of carbon nanotubes to chitosan, heteropolysaccharide and acetic acid is 1:(0.2-2):(0.1-0.2):(100-300); the mass ratio of surfactant to acetic acid solution is (1-5):(200-300).
[0012] Preferably, in step S1, the crosslinking agent is one of diphenylglyoxime, 3-ethoxybenzaldehyde, epichlorohydrin, 2-phenylpropylene oxide and polyacrylamide; the mass ratio of the crosslinking agent to chitosan is (0.1-0.5):1; the crosslinking reaction temperature is 50-90°C, and the time is 30-120min.
[0013] Preferably, in step S2, the cationic polyelectrolyte is one of polyethyleneimine, polyacrylamide, polyvinylpyrrole, and polydiallyldimethylammonium chloride; the organic solvent is one of ethanol solution, ethylene glycol solution, n-propanol solution, and isoamyl alcohol solution; the anionic polyelectrolyte is one of polymethacrylic acid, polystyrene sulfonic acid, polyethylene sulfonic acid, and carboxymethyl cellulose; and the mass ratio of graphite powder to cationic polyelectrolyte, anionic polyelectrolyte, and organic solvent is 1:(0.2-0.4):(0.1-0.4):(200-400).
[0014] Preferably, in step S2, the inert gas is one of nitrogen, argon and helium; the drying treatment temperature is 150-200°C and the time is 6-15h; the heat treatment temperature is 900-1100°C and the time is 2-6h.
[0015] Preferably, in step S3, the enhanced silane coupling agent is one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and 3-(methacryloxy)propyltrimethoxysilane, and the mass concentration of the enhanced silane coupling agent in the aqueous solution is 0.5%-5%; the mass ratio of chitosan film-coated carbon nanotubes, carbon-coated graphite and the enhanced silane coupling agent aqueous solution is (1-3): (0.5-2): (100-300); the hydrolysis catalyst is one of sodium hydroxide, ammonium chloride, ammonium tartrate, acetic acid sulfate and trimethylammonium chloride, and the mass ratio of the hydrolysis catalyst to the enhanced silane coupling agent aqueous solution is (1-2): (100-300).
[0016] Preferably, the drying heat treatment temperature in step S3 is 100-150° C. and the time is 50-80 min.
[0017] Preferably, in step S4, the resin powder is one of acrylic resin, polyurethane resin, epoxy resin and polyketone resin; the polymer additive is one of di(2-ethylhexyl) phthalate, polyvinyl chloride plasticizer, diisodecyl adipate and di(2-ethylhexyl) adipate; the organic solvent is one of ethanol solution, ethylene glycol solution, n-propanol solution and isoamyl alcohol solution; the mass ratio of resin powder, polymer additive and organic solvent is (5-10):(1-5):(30-50); the initial melt mixing temperature is 120-160°C, and the time is 10-50 min.
[0018] Preferably, the compatibilizer in step S4 is one of ethylene acrylic acid, ethylene-vinyl acetate copolymer, hydrogenated styrene-butadiene block copolymer and PE-g-ST maleic anhydride grafted polyolefin compatibilizer; the mass ratio of the banburying particles 1 and the paste filler and the compatibilizer is (15-30): (50-80): (1-5); the secondary melt mixing temperature is 180-250°C, and the time is 30-90min; the hot press integrated molding temperature is 180-220°C, the pressure is 80-100MPa, and the time is 10-30min.
[0019] A modified binary composite bipolar plate for a vanadium battery is prepared by using the above-mentioned method for preparing a modified binary composite bipolar plate for a vanadium battery.
[0020] The beneficial effects of the present invention are:
[0021] The present invention coats carbon nanotubes with chitosan membranes to achieve enhanced strength and improved stability of carbon nanotubes, while effectively limiting the strong van der Waals forces and pp bond interactions between carbon nanotubes, enhancing dispersibility, and reducing agglomeration and precipitation in subsequent slurries, thereby improving the dispersibility and uniformity of conductive carbon in bipolar plates, reducing contact resistance, and enhancing the strength of the bipolar plate itself.
[0022] The present invention performs carbon coating on graphite, wherein the carbon coating layer can form a continuous conductive network between graphite particles, reduce the charge transfer resistance on the graphite body, reduce the resistivity of the composite bipolar plate, and ensure the efficient flow of current inside the bipolar plate; in addition, the carbon coating layer can enhance the bonding force between graphite particles, improve the mechanical strength and overall stability of the composite bipolar plate, enhance its corrosion resistance, and extend the service life of the bipolar plate;
[0023] Through the action of enhanced silane coupling agent, chitosan film-modified carbon nanotubes and carbon-coated graphite are interface coupled to provide stronger interface bonding force, which means fewer interface defects and higher interface stability, which helps to improve the mechanical strength of the bipolar plate and can form a continuous conductive network, which can not only improve the conductivity of the bipolar plate, but also reduce the resistivity, thereby improving the efficiency of the all-vanadium liquid flow battery stack. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a flow chart of a method for preparing a modified binary composite bipolar plate for a vanadium battery. DETAILED DESCRIPTION
[0025] like Figure 1 As shown, a method for preparing a modified binary composite bipolar plate for a vanadium battery comprises the following steps:
[0026] Step S1: dispersing carbon nanotubes, chitosan and heteropolysaccharides in an acetic acid solution, and adding alkali solution and surfactant thereto to adjust the pH to 9-13 to obtain a precursor solution; placing the precursor solution in a water bath, and adding a crosslinking agent thereto to carry out a crosslinking reaction, after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes; the heteropolysaccharide is one of hyaluronic acid, chondroitin sulfate, agar and peptidoglycan, the mass ratio of carbon nanotubes to chitosan, heteropolysaccharide and acetic acid is 1: (0.2-2): (0.1-0.2): (100-300), the volume concentration of the acetic acid solution is 1%-5%; the alkali solution is one of ammonia solution, sodium carbonate solution, sodium hydroxide solution and triethylamine solution, and the concentration of the alkali solution is 0.5-2 mol / L; the surfactant is one of dodecyl dimethyl betaine, 3-sulfopropyl dodecyl dimethyl betaine, dodecyl aminopropionic acid and tetradecyl amide propyl hydroxypropyl sulfo betaine, and the mass ratio of the surfactant to the acetic acid solution is (1-5): (200-300); the crosslinking agent is one of diphenyl glyoxime, 3-ethoxybenzaldehyde, epichlorohydrin, 2-phenylpropylene oxide and polyacrylamide, the crosslinking reaction temperature is 50-90℃, the crosslinking reaction time is 30-120 min, and the mass ratio of the crosslinking agent to chitosan is (0.1-0.5): 1;
[0027] Step S2: dispersing graphite powder and cationic polyelectrolyte in an organic solvent, then adding anionic polyelectrolyte thereto and stirring and reacting under the protection of inert gas, filtering and washing the obtained product, transferring it to an oven for drying, and then heat-treating the obtained product under the protection of inert gas to obtain carbon-coated graphite; the cationic polyelectrolyte is one of polyethyleneimine, polyacrylamide, polyvinylpyrrole, and polydiallyldimethylammonium chloride; the organic solvent is one of ethanol solution, ethylene glycol solution, n-propanol solution and isoamyl alcohol solution; the anionic polyelectrolyte is one of polymethacrylic acid, polystyrene sulfonic acid, polyethylene sulfonic acid and carboxymethyl cellulose; the mass ratio of graphite powder to cationic polyelectrolyte, anionic polyelectrolyte and organic solvent is 1:(0.2- 0.4): (0.1-0.4): (200-400); the inert gas is one of nitrogen, argon and helium, the drying temperature is 150-200℃, the time is 6-15h, the heat treatment temperature is 900-1100℃, the time is 2-6h;
[0028] Step S3: Grind and disperse the chitosan film-coated carbon nanotubes and carbon-coated graphite to obtain a mixed binary carbon material, and disperse it in an enhanced silane coupling agent aqueous solution and stir and disperse it, then add a hydrolysis catalyst and continue stirring, and after the reaction is completed, transfer it to an oven for drying and heat treatment to obtain a paste slurry; the mass ratio of the chitosan film-coated carbon nanotubes, the carbon-coated graphite and the enhanced silane coupling agent aqueous solution is (1-3): (0.5-2): (100-300), and the enhanced silane coupling agent is γ-aminopropyltriethoxysilane, γ- One of glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane and 3-(methacryloxy)propyl trimethoxysilane, the mass concentration of which in the enhanced silane coupling agent aqueous solution is 0.5%-5%; the hydrolysis catalyst is one of sodium hydroxide, ammonium chloride, ammonium tartrate, acetic acid sulfate and trimethylammonium chloride, the mass ratio of the hydrolysis catalyst to the enhanced silane coupling agent aqueous solution is (1-2): (100-300); the drying heat treatment temperature is 100-150°C, and the drying heat treatment time is 50-80 min;
[0029] Step S4: first disperse the resin powder and the polymer additive in an organic solvent, and perform preliminary melt mixing in an internal mixer to obtain internal mixer particles 1, then melt mix the internal mixer particles 1 and the paste filler and the compatibilizer again in the internal mixer to obtain internal mixer particles 2, transfer the internal mixer particles 2 to a mold and perform integral molding with a hot press to obtain a modified binary composite bipolar plate; the resin powder is one of acrylic resin, polyurethane resin, epoxy resin and polyketone resin, the polymer additive is one of di(2-ethylhexyl) phthalate, polyvinyl chloride plasticizer, diisodecyl adipate and di(2-ethylhexyl) adipate, and the organic solvent is ethanol solution, ethylene glycol solution, n-propanol solution and isoamyl alcohol solution The invention relates to a kind of liquid, the mass ratio of resin powder, polymer additive and organic solvent is (5-10): (1-5): (30-50), the initial melt mixing temperature is 120-160°C, and the time is 10-50min; the compatibilizer is one of ethylene acrylic acid, ethylene-vinyl acetate copolymer, hydrogenated styrene-butadiene block copolymer and PE-g-ST maleic anhydride grafted polyolefin compatibilizer, the mass ratio of banburying particles 1 and paste filler and compatibilizer is (15-30): (50-80): (1-5), the secondary melt mixing temperature is 180-250°C, and the time is 30-90min; the hot press integrated molding temperature is 180-220°C, the pressure is 80-100 MPa, and the time is 10-30min.
[0030] Example 1: A method for preparing a modified binary composite bipolar plate for a vanadium battery, comprising the following steps:
[0031] Step S1: dispersing carbon nanotubes, chitosan and hyaluronic acid in an acetic acid solution with a volume concentration of 1%, and adding 1 mol / L ammonia water and 3-sulfopropyl dodecyl dimethyl betaine thereto to adjust the pH to 9 to obtain a precursor solution, wherein the mass ratio of carbon nanotubes, chitosan, hyaluronic acid and acetic acid solution is 1:0.2:0.2:300, and the mass ratio of 3-sulfopropyl dodecyl dimethyl betaine to acetic acid solution is 1:200; placing the precursor solution in a 90°C water bath, and adding diphenyl glyoxime thereto for cross-linking reaction, after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes, wherein the mass ratio of diphenyl glyoxime to chitosan is 0.1:1, and the cross-linking time is 120 min;
[0032] Step S2: dispersing graphite powder and polyvinyl pyrrole in an ethanol solution, then adding carboxymethyl cellulose thereto and stirring the solution under nitrogen protection, filtering and washing the obtained product, transferring it to an oven and drying it at 150° C. for 15 h, and then heat-treating the obtained product under nitrogen protection at a temperature of 900° C. for 6 h to obtain carbon-coated graphite; wherein the mass ratio of graphite powder, polyvinyl pyrrole, carboxymethyl cellulose to the ethanol solution is 1:0.2:0.1:200;
[0033] Step S3: Grind and disperse the chitosan film-coated carbon nanotubes and carbon-coated graphite to obtain a mixed binary carbon material, and disperse it in a 0.5% γ-methacryloxypropyltrimethoxysilane aqueous solution and stir and disperse it, then add ammonium chloride and continue stirring, and after the reaction is completed, transfer it to an oven for drying and heat treatment at a temperature of 150°C for 60 min to obtain a paste slurry; wherein the mass ratio of the chitosan film-coated carbon nanotubes, the carbon-coated graphite and the γ-methacryloxypropyltrimethoxysilane aqueous solution is 1:0.5:100, and the mass ratio of ammonium chloride to the γ-methacryloxypropyltrimethoxysilane aqueous solution is 1:100;
[0034] Step S4: first disperse the acrylic resin and the polyvinyl chloride plasticizer in the n-propanol solution, and perform preliminary melt mixing in an internal mixer to obtain internal mixer particles 1, wherein the mass ratio of the acrylic resin, the polyvinyl chloride plasticizer and the n-propanol solution is 5:1:30, the preliminary melt mixing temperature is 120°C, and the time is 50 min; then, the internal mixer particles 1 and the paste filler and the ethylene-vinyl acetate copolymer are melt mixed again in the internal mixer to obtain internal mixer particles 2, wherein the mass ratio of the internal mixer particles 1, the paste filler and the ethylene-vinyl acetate copolymer is 15:50:1, the secondary melt mixing temperature is 180°C, and the time is 90 min; the internal mixer particles 2 are transferred to the mold and integrally molded by a hot press, wherein the hot press molding temperature is 220°C, the pressure is 100 MPa, and the time is 10 min, to obtain a modified binary composite bipolar plate.
[0035] Example 2: A method for preparing a modified binary composite bipolar plate for a vanadium battery, comprising the following steps:
[0036] Step S1: dispersing carbon nanotubes, chitosan and chondroitin sulfate in an acetic acid solution with a volume concentration of 3%, and adding 2 mol / L sodium carbonate solution and dodecyl dimethyl betaine thereto to adjust the pH to 10 to obtain a precursor solution, wherein the mass ratio of carbon nanotubes, chitosan, chondroitin sulfate and acetic acid solution is 1:2:0.1:100, and the mass ratio of dodecyl dimethyl betaine to acetic acid solution is 3:250; placing the precursor solution in an 80°C water bath, and adding 3-ethoxybenzaldehyde thereto for cross-linking reaction, after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes, wherein the mass ratio of 3-ethoxybenzaldehyde to chitosan is 0.5:1, and the cross-linking time is 60 min;
[0037] Step S2: dispersing graphite powder and polyethyleneimine in an ethylene glycol solution, then adding polystyrene sulfonic acid thereto and stirring the reaction under argon protection, filtering and washing the obtained product, transferring it to an oven and drying it at 170°C for 12 h, and then heat-treating the obtained product under argon protection at a heat treatment temperature of 1000°C for 4 h to obtain carbon-coated graphite; the mass ratio of the graphite powder, polyethyleneimine, polystyrene sulfonic acid to the ethylene glycol solution is 1:0.4:0.4:400;
[0038] Step S3: Grind and disperse the chitosan film-coated carbon nanotubes and carbon-coated graphite to obtain a mixed binary carbon material, and disperse it in a 2% γ-aminopropyltriethoxysilane aqueous solution and stir and disperse it, then add sodium hydroxide and continue stirring, and after the reaction is completed, transfer it to an oven for drying and heat treatment at a temperature of 130°C for 50 min to obtain a paste slurry; wherein the mass ratio of the chitosan film-coated carbon nanotubes, the carbon-coated graphite and the γ-aminopropyltriethoxysilane aqueous solution is 1:2:300, and the mass ratio of the sodium hydroxide and the γ-aminopropyltriethoxysilane aqueous solution is 2:100;
[0039] Step S4: first disperse epoxy resin and diisodecyl adipate in isoamyl alcohol solution, and perform preliminary melt mixing in an internal mixer to obtain internal mixer particles 1, wherein the mass ratio of epoxy resin, diisodecyl adipate and isoamyl alcohol solution is 5:5:30, the preliminary melt mixing temperature is 130°C, and the time is 40 min; then, the internal mixer particles 1 and the paste filler and ethylene acrylic acid are melt mixed again in the internal mixer to obtain internal mixer particles 2, wherein the mass ratio of the internal mixer particles 1, the paste filler and ethylene acrylic acid is 15:80:5, the secondary melt mixing temperature is 200°C, and the time is 60 min; the internal mixer particles 2 are transferred to the mold and integrally pressed by a hot press, wherein the hot press molding temperature is 200°C, the pressure is 90 MPa, and the time is 20 min to obtain a modified binary composite bipolar plate.
[0040] Example 3: A method for preparing a modified binary composite bipolar plate for a vanadium battery, comprising the following steps:
[0041] Step S1: dispersing carbon nanotubes, chitosan and agar in an acetic acid solution with a volume concentration of 5%, and adding 0.5 mol / L sodium hydroxide solution and dodecylaminopropionic acid thereto to adjust the pH to 11 to obtain a precursor solution, wherein the mass ratio of carbon nanotubes, chitosan, agar and acetic acid solution is 1:1:0.15:200, and the mass ratio of dodecylaminopropionic acid to acetic acid solution is 5:200; placing the precursor solution in a 70°C water bath, and adding 2-phenylpropylene oxide thereto for cross-linking reaction, after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes, wherein the mass ratio of 2-phenylpropylene oxide to chitosan is 0.3:1, and the cross-linking time is 30 min;
[0042] Step S2: dispersing graphite powder and polydiallyldimethylammonium chloride in an isoamyl alcohol solution, then adding polymethacrylic acid thereto and stirring the reaction under the protection of helium, filtering and washing the obtained product, transferring it to an oven and drying it at 190°C for 9 hours, and then heat-treating the obtained product under the protection of helium at a temperature of 1100°C for 2 hours to obtain carbon-coated graphite; the mass ratio of the graphite powder, polydiallyldimethylammonium chloride, polymethacrylic acid and isoamyl alcohol solution is 1:0.3:0.1:200;
[0043] Step S3: Grind and disperse the chitosan film-coated carbon nanotubes and carbon-coated graphite to obtain a mixed binary carbon material, and disperse it in a 3% 3-(methacryloyloxy)propyltrimethoxysilane aqueous solution and stir and disperse it, then add trimethylammonium chloride and continue stirring, and after the reaction is completed, transfer it to an oven for drying and heat treatment at a temperature of 110°C for 70 min to obtain a paste slurry; wherein the mass ratio of the chitosan film-coated carbon nanotubes, the carbon-coated graphite and the 3-(methacryloyloxy)propyltrimethoxysilane aqueous solution is 3:0.5:200, and the mass ratio of trimethylammonium chloride to the 3-(methacryloyloxy)propyltrimethoxysilane aqueous solution is 1:300;
[0044] Step S4: firstly disperse the polyurethane resin and di(2-ethylhexyl) phthalate in the ethylene glycol solution, and perform preliminary melt mixing in the internal mixer to obtain internal mixer particles 1, wherein the mass ratio of the polyurethane resin, di(2-ethylhexyl) phthalate and the ethylene glycol solution is 10:1:50, the preliminary melt mixing temperature is 140°C, and the time is 30 min; then, the internal mixer particles 1 and the paste filler and the PE-g-ST maleic anhydride grafted polyolefin compatibilizer are melt mixed again in the internal mixer to obtain internal mixer particles 2, wherein the mass ratio of the internal mixer particles 1, the paste filler and the PE-g-ST maleic anhydride grafted polyolefin compatibilizer is 30:80:1, the secondary melt mixing temperature is 220°C, and the time is 30 min; the internal mixer particles 2 are transferred to the mold and integrally molded by a hot press, wherein the hot press molding temperature is 180°C, the pressure is 80 MPa, and the time is 30 min, and a modified binary composite bipolar plate was obtained.
[0045] Example 4: A method for preparing a modified binary composite bipolar plate for a vanadium battery, comprising the following steps:
[0046] Step S1: dispersing carbon nanotubes, chitosan and hyaluronic acid in an acetic acid solution with a volume concentration of 2%, and adding 1.5 mol / L triethylamine solution and 3-sulfopropyl dodecyl dimethyl betaine thereto to adjust the pH to 13 to obtain a precursor solution, wherein the mass ratio of carbon nanotubes, chitosan, hyaluronic acid and acetic acid solution is 1:0.5:0.1:150, and the mass ratio of 3-sulfopropyl dodecyl dimethyl betaine to acetic acid solution is 1:300; placing the precursor solution in a 60°C water bath, and adding polyacrylamide thereto for cross-linking reaction, after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes, wherein the mass ratio of polyacrylamide to chitosan is 0.4:1, and the cross-linking time is 90 min;
[0047] Step S2: dispersing graphite powder and polyvinyl pyrrole in an ethylene glycol solution, then adding polyethylene sulfonic acid thereto and stirring the reaction under nitrogen protection, filtering and washing the obtained product, transferring it to an oven and drying it at 200°C for 6 hours, and then heat-treating the obtained product under nitrogen protection at a temperature of 950°C for 3 hours to obtain carbon-coated graphite; the mass ratio of graphite powder, polyvinyl pyrrole, polyethylene sulfonic acid to ethylene glycol solution is 1:0.4:0.1:400;
[0048] Step S3: Grind and disperse the chitosan film-coated carbon nanotubes and carbon-coated graphite to obtain a mixed binary carbon material, and disperse it in a 5% γ-glycidyloxypropyltrimethoxysilane aqueous solution and stir and disperse it, then add ammonium tartrate and continue stirring, and after the reaction is completed, transfer it to an oven for drying and heat treatment at a temperature of 140°C for 60 min to obtain a paste slurry; wherein the mass ratio of the chitosan film-coated carbon nanotubes, the carbon-coated graphite and the γ-glycidyloxypropyltrimethoxysilane aqueous solution is 3:2:200, and the mass ratio of ammonium tartrate to the γ-glycidyloxypropyltrimethoxysilane aqueous solution is 2:300;
[0049] Step S4: firstly disperse the polyketone resin and di(2-ethylhexyl) adipate in a n-propanol solution, and perform preliminary melt mixing in an internal mixer to obtain internal mixer particles 1, wherein the mass ratio of the polyketone resin, di(2-ethylhexyl) adipate and the n-propanol solution is 10:5:30, the preliminary melt mixing temperature is 150°C, and the time is 20 min; then, the internal mixer particles 1 and the paste filler and the hydrogenated styrene-butadiene block copolymer are melt mixed again in an internal mixer to obtain internal mixer particles 2, wherein the mass ratio of the internal mixer particles 1, the paste filler and the hydrogenated styrene-butadiene block copolymer is 30:50:5, the secondary melt mixing temperature is 250°C, and the time is 50 min; the internal mixer particles 2 are transferred to a mold and integrally pressed by a hot press, wherein the hot press molding temperature is 190°C, the pressure is 85 MPa, and the time is 15 min, to obtain a modified binary composite bipolar plate.
[0050] Example 5: A method for preparing a modified binary composite bipolar plate for a vanadium battery, comprising the following steps:
[0051] Step S1: dispersing carbon nanotubes, chitosan and peptidoglycan in an acetic acid solution with a volume concentration of 4%, and adding 1 mol / L ammonia solution and tetradecanoyl amide propyl hydroxypropyl sulfobetaine thereto to adjust the pH to 12 to obtain a precursor solution, wherein the mass ratio of carbon nanotubes, chitosan, peptidoglycan and acetic acid solution is 1:1.5:0.1:250, and the mass ratio of tetradecanoyl amide propyl hydroxypropyl sulfobetaine to acetic acid solution is 5:300; placing the precursor solution in a 50°C water bath, and adding epichlorohydrin thereto for cross-linking reaction, after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes, wherein the mass ratio of epichlorohydrin to chitosan is 0.2:1, and the cross-linking time is 45 min;
[0052] Step S2: dispersing graphite powder and polydiallyldimethylammonium chloride in a n-propanol solution, then adding polymethacrylic acid thereto and stirring the reaction under the protection of helium, filtering and washing the obtained product, transferring it to an oven and drying it at 160° C. for 16 h, and then heat-treating the obtained product under the protection of helium at a temperature of 1050° C. for 5 h to obtain carbon-coated graphite; the mass ratio of the graphite powder, polydiallyldimethylammonium chloride, polymethacrylic acid and n-propanol solution is 1:0.2:0.4:400;
[0053] Step S3: Grind and disperse the chitosan film-coated carbon nanotubes and carbon-coated graphite to obtain a mixed binary carbon material, and disperse it in a 4% 3-(methacryloyloxy)propyltrimethoxysilane aqueous solution and stir and disperse it, then add acetic acid sulfate and continue stirring, and after the reaction is completed, transfer it to an oven for drying and heat treatment at a temperature of 150°C for 50 min to obtain a paste slurry; wherein the mass ratio of the chitosan film-coated carbon nanotubes, the carbon-coated graphite and the 3-(methacryloyloxy)propyltrimethoxysilane aqueous solution is 2:1:150, and the mass ratio of acetic acid sulfate and the 3-(methacryloyloxy)propyltrimethoxysilane aqueous solution is 2:250;
[0054] Step S4: First, disperse the epoxy resin and diisodecyl adipate in an ethanol solution, and perform preliminary melt mixing in an internal mixer to obtain internal mixer particles 1, wherein the mass ratio of the epoxy resin, diisodecyl adipate and the ethanol solution is 5:5:50, the preliminary melt mixing temperature is 160°C, and the time is 10 min; then, the internal mixer particles 1 and the paste filler and the PE-g-ST maleic anhydride grafted polyolefin compatibilizer are melt mixed again in the internal mixer to obtain internal mixer particles 2, wherein the mass ratio of the internal mixer particles 1, the paste filler and the PE-g-ST maleic anhydride grafted polyolefin compatibilizer is 20:50:5, the secondary melt mixing temperature is 230°C, and the time is 60 min; the internal mixer particles 2 are transferred to a mold and integrally molded by a hot press, wherein the hot press molding temperature is 210°C, the pressure is 100 MPa, and the time is 25 min to obtain a modified binary composite bipolar plate.
[0055] Example 6: A method for preparing a modified binary composite bipolar plate for a vanadium battery, comprising the following steps:
[0056] Step S1: dispersing carbon nanotubes, chitosan and agar in an acetic acid solution with a volume concentration of 1%, and adding 2 mol / L sodium carbonate solution and tetradecanoyl amide propyl hydroxypropyl sulfobetaine thereto to adjust the pH to 13 to obtain a precursor solution, wherein the mass ratio of carbon nanotubes, chitosan, agar and acetic acid solution is 1:0.8:0.2:300, and the mass ratio of tetradecanoyl amide propyl hydroxypropyl sulfobetaine to acetic acid solution is 2:250; placing the precursor solution in a 70°C water bath, and adding 2-phenylpropylene oxide thereto for cross-linking reaction, after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes, wherein the mass ratio of 2-phenylpropylene oxide to chitosan is 0.3:1, and the cross-linking time is 75 min;
[0057] Step S2: dispersing graphite powder and polyacrylamide in an ethanol solution, then adding polystyrene sulfonic acid thereto and stirring the reaction under argon protection, filtering and washing the obtained product, transferring it to an oven and drying it at 180°C for 11 hours, and then heat-treating the obtained product under argon protection at a heat treatment temperature of 1100°C for 3 hours to obtain carbon-coated graphite; the mass ratio of the graphite powder, polyacrylamide, polystyrene sulfonic acid to the ethanol solution is 1:0.2:0.1:200;
[0058] Step S3: Grind and disperse the chitosan film-coated carbon nanotubes and carbon-coated graphite to obtain a mixed binary carbon material, and disperse it in a 4% γ-aminopropyltriethoxysilane aqueous solution and stir and disperse it, then add trimethylammonium chloride and continue stirring, and after the reaction is completed, transfer it to an oven for drying and heat treatment at a temperature of 100°C for 90 min to obtain a paste slurry; wherein the mass ratio of the chitosan film-coated carbon nanotubes, the carbon-coated graphite and the γ-aminopropyltriethoxysilane aqueous solution is 1:1:300, and the mass ratio of the trimethylammonium chloride and the γ-aminopropyltriethoxysilane aqueous solution is 2:150;
[0059] Step S4: first disperse the polyurethane resin and di(2-ethylhexyl) phthalate in the ethylene glycol solution, and perform preliminary melt mixing in an internal mixer to obtain internal mixer particles 1, wherein the mass ratio of the polyurethane resin, di(2-ethylhexyl) phthalate and the ethylene glycol solution is 10:1:30, the preliminary melt mixing temperature is 130°C, and the time is 25 min; then, the internal mixer particles 1 and the paste filler and the hydrogenated styrene-butadiene block copolymer are melt mixed again in the internal mixer to obtain internal mixer particles 2, wherein the mass ratio of the internal mixer particles 1, the paste filler and the hydrogenated styrene-butadiene block copolymer is 25:80:1, the secondary melt mixing temperature is 190°C, and the time is 40 min; the internal mixer particles 2 are transferred to the mold and integrally molded by a hot press, wherein the hot press molding temperature is 220°C, the pressure is 100 MPa, and the time is 30 min, to obtain a modified binary composite bipolar plate.
[0060] Comparative Example 1: The preparation process of this comparative example is different from that of Example 1 only in that unmodified carbon nanotubes are used.
[0061] Comparative Example 2: The preparation process of this comparative example is different from that of Example 1 only in that unmodified graphite powder is used.
[0062] Comparative Example 3: The preparation process of this comparative example is different from that of Example 1 only in that no enhanced silane coupling agent and no hydrolysis catalyst are used in step S3.
[0063] The industry standard NB / T42007-2013 "Test Method for Bipolar Plates for All-vanadium Liquid Flow Batteries" was adopted to test the performance of bipolar plates of the embodiments and comparative examples of the present invention. The bipolar plates prepared in embodiments 1-6 and comparative examples 1-3 were cut into a size of 5 cm×5 cm, and the conductivity of the bipolar plates was tested using a ST2258C digital four-probe. The bipolar plates prepared in embodiments 1-6 and comparative examples 1-3 were cut into a size of 10 cm×2 cm, and the bending strength of the samples was determined by a three-point bending test using a mechanical testing machine. The tensile strength of the composite bipolar plates was measured at a loading speed of 1 mm / min, and 5 samples were tested in each group to take the average value. The three-point bending method was used to test the bending strength of the composite plate. The support span was adjusted so that the pressure head and the support head were perpendicular to the sample axis, and the pressure head was loaded at a speed of 10 mm / s. 2 The load is applied uniformly and without impact until the sample breaks, and the breaking load value is read.
[0064] The examples 1-6 and the comparative examples 1-3 were assembled into a battery stack for testing. The test current density was 80 mA / cm 2 , record the coulombic efficiency, energy efficiency and voltage efficiency. The test results are shown in Table 1:
[0065] Table 1 Bipolar plate and stack performance test results
[0066]
[0067] As can be seen from Table 1, compared with Comparative Examples 1 and 2, Examples 1-6 have lower electrical conductivity, higher tensile strength and higher flexural strength. This may be due to the fact that the chitosan film is tightly combined with the carbon nanotubes through non-covalent bonds to form a stable composite material. The coating of the carbon nanotubes provides them with an efficient electron transport medium, protecting the conductive channels of the carbon nanotubes from damage by the external environment. The carbon-coated graphite structure also reduces the transmission resistance of electrons between conductive fillers, which is beneficial to the improvement of the conductivity of the composite bipolar plate. The two modified carbon materials provide a more efficient electron transport medium inside the bipolar plate, improve the conductivity of the bipolar plate, and provide a fast path for the conduction of electrons in the vanadium flow battery, thereby enhancing its coulombic efficiency, energy efficiency and voltage efficiency in the vanadium flow battery. The coupling agent couples the modified binary materials to utilize the high strength characteristics of the chitosan film and the carbon coating structure to achieve the mechanical strength of the bipolar plate. of the comparative example 3, thereby enhancing its tensile and compressive strengths and ensuring its stability; compared with comparative example 3, examples 1-6 show higher electrical conductivity, higher tensile strength and higher flexural strength. The higher electrical conductivity may be due to the chitosan organic film introduced on the surface of the carbon nanotubes and the carbon-coated graphite structure providing a faster electron transmission channel for the bipolar plate, thereby improving the conductivity of the modified binary composite bipolar plate. Due to the lack of the chitosan organic film on the surface of the carbon nanotubes and the coated carbon structure of the graphite, comparative example 3 cannot achieve an effective combination of the two through a silane coupling agent, resulting in a decrease in the strength of the prepared bipolar plate body and an inability to withstand large tensile and bending forces. This indicates that the coupling effect of binary carbon achieved through a coupling agent can enable the binary carbon components to be tightly connected, effectively improving the mechanical strength of the bipolar plate, thereby achieving its energy efficiency and voltage efficiency in an all-vanadium liquid flow battery, and improving its liquid flow battery performance.
Claims
1. A method for preparing a modified binary composite bipolar plate for a vanadium battery, characterized in that: At least the following steps are included: Step S1: dispersing carbon nanotubes, chitosan and heteropolysaccharides in an acetic acid solution, and adding an alkali solution and a surfactant thereto to adjust the pH to 9-13 to obtain a precursor solution; placing the precursor solution in a water bath, and adding a crosslinking agent thereto to carry out a crosslinking reaction, and after the reaction is completed, filtering and washing and drying the precipitate to obtain chitosan film-coated carbon nanotubes; Step S2: dispersing graphite powder and cationic polyelectrolyte in an organic solvent, then adding anionic polyelectrolyte thereto and stirring and reacting under the protection of an inert gas, filtering and washing the obtained product, and transferring it to an oven for drying, and then heat-treating the obtained product under the protection of an inert gas to obtain carbon-coated graphite; Step S3: Grind and disperse the chitosan film-coated carbon nanotubes and the carbon-coated graphite to obtain a mixed binary carbon material, and disperse the mixed binary carbon material in an enhanced silane coupling agent aqueous solution and stir and disperse the mixed binary carbon material, then add a hydrolysis catalyst thereto and continue stirring, and after the reaction is completed, transfer the mixed binary carbon material to an oven for drying and heat treatment to obtain a paste filler; the enhanced silane coupling agent is one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane and 3-(methacryloxy)propyl trimethoxysilane; Step S4: First, disperse the resin powder and the polymer additive in an organic solvent, and perform preliminary melt mixing in an internal mixer to obtain internal mixer particles 1. Then, the internal mixer particles 1 and the paste filler and the compatibilizer are melt mixed again in the internal mixer to obtain internal mixer particles 2. The internal mixer particles 2 are transferred to a mold and integrally pressed with a hot press to obtain a modified binary composite bipolar plate.
2. The method for preparing a modified binary composite bipolar plate for a vanadium battery according to claim 1, characterized in that: In step S1, the heteropolysaccharide is one of hyaluronic acid, chondroitin sulfate, agar and peptidoglycan; the volume concentration of the acetic acid solution is 1%-5%; the alkali solution is one of ammonia solution, sodium carbonate solution, sodium hydroxide solution and triethylamine solution, and the concentration is 0.5-2 mol / L; the surfactant is one of dodecyl dimethyl betaine, 3-sulfopropyl dodecyl dimethyl betaine, dodecyl aminopropionic acid and tetradecanoyl amide propyl hydroxypropyl sulfobetaine; the mass ratio of carbon nanotubes to chitosan, heteropolysaccharide and acetic acid is 1:(0.2-2):(0.1-0.2):(100-300); the mass ratio of the surfactant to the acetic acid solution is (1-5):(200-300).
3. The method for preparing a modified binary composite bipolar plate for a vanadium battery according to claim 1, characterized in that: In step S1, the crosslinking agent is one of diphenylglyoxime, 3-ethoxybenzaldehyde, epichlorohydrin, 2-phenylpropylene oxide and polyacrylamide; the mass ratio of the crosslinking agent to chitosan is (0.1-0.5):1; the crosslinking reaction temperature is 50-90°C and the time is 30-120min.
4. The method for preparing a modified binary composite bipolar plate for a vanadium battery according to claim 1, characterized in that: In step S2, the cationic polyelectrolyte is one of polyethyleneimine, polyacrylamide, polyvinylpyrrole, and polydiallyldimethylammonium chloride; the organic solvent is one of ethanol solution, ethylene glycol solution, n-propanol solution, and isoamyl alcohol solution; the anionic polyelectrolyte is one of polymethacrylic acid, polystyrene sulfonic acid, polyethylene sulfonic acid, and carboxymethyl cellulose; and the mass ratio of graphite powder to cationic polyelectrolyte, anionic polyelectrolyte, and organic solvent is 1:(0.2-0.4):(0.1-0.4):(200-400).
5. The method for preparing a modified binary composite bipolar plate for a vanadium battery according to claim 1, characterized in that: In step S2, the inert gas is one of argon and helium; the drying treatment temperature is 150-200°C and the time is 6-15h; the heat treatment temperature is 900-1100°C and the time is 2-6h.
6. The method for preparing a modified binary composite bipolar plate for a vanadium battery according to claim 1, characterized in that: In step S3, the mass concentration of the enhanced silane coupling agent in the aqueous solution is 0.5%-5%; the mass ratio of chitosan film-coated carbon nanotubes, carbon-coated graphite and the enhanced silane coupling agent aqueous solution is (1-3): (0.5-2): (100-300); the hydrolysis catalyst is one of sodium hydroxide, ammonium chloride, ammonium tartrate, acetic acid sulfate and trimethylammonium chloride, and the mass ratio of the hydrolysis catalyst to the enhanced silane coupling agent aqueous solution is (1-2): (100-300).
7. The method for preparing a modified binary composite bipolar plate for a vanadium battery according to claim 1, characterized in that: In step S3, the drying heat treatment temperature is 100-150° C. and the time is 50-80 min.
8. The method for preparing a modified binary composite bipolar plate for a vanadium battery according to claim 1, characterized in that: In step S4, the resin powder is one of acrylic resin, polyurethane resin, epoxy resin and polyketone resin; the polymer additive is one of di(2-ethylhexyl) phthalate, polyvinyl chloride plasticizer, diisodecyl adipate and di(2-ethylhexyl) adipate; the organic solvent is one of ethanol solution, ethylene glycol solution, n-propanol solution and isoamyl alcohol solution; the mass ratio of the resin powder, the polymer additive and the organic solvent is (5-10):(1-5):(30-50); the initial melt mixing temperature is 120-160°C and the time is 10-50min.
9. The method for preparing a modified binary composite bipolar plate for a vanadium battery according to claim 1, characterized in that: In step S4, the compatibilizer is one of ethylene acrylic acid, ethylene-vinyl acetate copolymer, hydrogenated styrene-butadiene block copolymer and PE-g-ST maleic anhydride grafted polyolefin compatibilizer; the mass ratio of the banburying particles 1 and the paste filler and the compatibilizer is (15-30): (50-80): (1-5); the secondary melt mixing temperature is 180-250°C, and the time is 30-90min; the hot press integrated molding temperature is 180-220°C, the pressure is 80-100MPa, and the time is 10-30min.
10. A modified binary composite bipolar plate for vanadium battery, characterized in that: The composite bipolar plate is prepared by the method for preparing a modified binary composite bipolar plate for a vanadium battery as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of bipolar plate based on PPS
CN116565245A
Process for producing carbon-cladded composite bipolar plates for fuel cells
US20080149900A1
Cited By
High-strength flexible bipolar plate and preparation method thereof
CN122356521A
Preparation method of a toughened bipolar plate and application thereof in a vanadium redox flow battery
CN122868569A